Pengintegrasian Critical Spiritual Pedagogy dalam Pembelajaran Bahasa Inggris:: Penyuluhan melalui Webinar yang Diselenggarakan oleh UIN Syarif Hidayatullah Jakarta - Joseph Ernest Mambu (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
Motivated by the need to incorporate spirituality into pedagogical practices, Technical Implementation Unit, Language Development Center, State Islamic University Syarif Hidayatullah Jakarta invited the author to share his experiences investigating Critical Spiritual Pedagogy (CSP) and its integration into English language learning. Attended by 47 people, some of whom were English school teachers and university lecturers, the author, as a resource person in a webinar, presented concepts of criticality and spirituality before elaborating on CSP and its pedagogical implementations in English language classrooms. Based on pre- and post-presentation questionnaires and a question-and-answer session, it can be concluded that CSP was considered essential. Overall, participants also thought that CSP could be developed further for English language learning.